Equity Policy and Participation in Australian Higher Education - Koshy, Paul Malcolm (Curtin University, 2018)
This thesis undertakes an analysis of key issues in Australian higher education equity policy in view of current policy settings and empirical research on the determinants of undergraduate higher education participation. Equity policy is defined to include government initiatives to promote higher education participation amongst groups who have been historically disadvantaged in their access (‘equity student groups’) and the categorisation and measurement tools used to identify students belonging to these groups.